MEDIA CONSTRUCTION OF ERICK THOHIR IN DETERMINING THE COMMISSIONERS OF STATE-OWNED ENTERPRISES (BUMN) - Radita Gora; Munadhil Abdul Muqsith; Barek Hossain (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2022)
Abstract. This paper aims to analyze the media in the intrigue of political interests in determining the commissioners and leadership ranks of State-Owned Enterprises (BUMN) by the Minister of BUMN, Erick Tohir, was colored by the paradigm of State company management which was fundamentally overhauled but full of the stigma that favored the political elite in power. This was built by Tempo magazine in two editions, which both reported on the steps and actions of Erick Thohir in reshuffling the leadership ranks in BUMN. The theory of media reality construction is used in this study to dissect the construction of media coverage and the method used, namely framing analysis with Pan and Kosicki framing analysis models to analyze the structure of the text on Tempo magazine news in terms of media ideology and political economy interests. It was found that Tempo emphasized facts through news frames which always emphasized that the reshuffle of the leadership in BUMN had become a political matter. There was the involvement of parties close to Erick Thohir and entrusting personal or figures close to Jokowi to occupy the ranks of commissioners and directors in Indonesia. BUMN.Keyword: Erick Thohir, News Framing, Political Imagery, SOE Officials Reshuffle Abstrak.Tulisan ini bertujuan untuk menganalisis media dalam intrik kepentingan politik dalam penetapan komisaris dan jajaran pimpinan Badan Usaha Milik Negara (BUMN) oleh Menteri BUMN, Erick Tohir, diwarnai dengan paradigma pengelolaan perusahaan negara yang dirombak secara fundamental. namun penuh dengan stigma yang berpihak pada elit politik yang berkuasa. Hal itu dibangun majalah Tempo dalam dua edisi, yang sama-sama memberitakan langkah dan tindakan Erick Thohir dalam perombakan jajaran pimpinan di BUMN. Teori konstruksi realitas media digunakan dalam penelitian ini untuk membedah konstruksi pemberitaan media dan metode yang digunakan yaitu analisis framing dengan model analisis framing Pan dan Kosicki untuk menganalisis struktur teks berita majalah Tempo ditinjau dari ideologi media dan kepentingan ekonomi politik. Ditemukan Tempo menekankan fakta melalui bingkai berita yang selalu menekankan bahwa perombakan pimpinan di BUMN sudah menjadi urusan politik. Ada keterlibatan pihak dekat Erick Thohir dan menitipkan pribadi atau tokoh dekat Jokowi untuk menduduki jajaran komisaris dan direksi di Indonesia. BUMN.Kata Kunci: Citra Politik, Erick Thohir, Framing Berita, Reshuffle Pejabat BUMN